Efektivitas Citicoline terhadap Perbaikan Status Fungsional dan Gangguan Neurologis pada Pasien dengan Stroke Perdarahan Intraserebral Supratentorial Akut - Ariel Valentino Soetedjo (PT Kalbe Farma Tbk., 2024)
Supratentorial intracerebral hemorrhage (ICH) is the second most common stroke and can potentially have poor outcomes. Citicoline has been researched extensively for ischemic stroke yet has little evidence for hemorrhagic stroke. This study aims to critically appraise evidence regarding efficacy of citicoline in improving functional status and neurological deficit in supratentorial ICH. The literature search utilized 5 databases: PubMed, Embase, Cochrane, Scopus, EBSCOHost. From 802 studies identified at the start of the search, 5 articles were selected for critical appraisal. A study by Zang demonstrated improvement in the NIHSS score (p=0.015) and Barthel index (p=0.001). A study by Mousavi showed improvement in the Barthel index (p=0.008) when compared to the control, but no difference when compared to the baseline in both groups. A study by Iranmanesh demonstrated improvement in the motoric strength (p=0.019). A study by Chua demonstrated improvement in the Barthel index at 3 months follow-up (p<0.05). However, there are no differences in the modified Rankin scale and NIHSS score. A study by Secades demonstrated improvement in the NIHSS score (p<0.001) when compared to baseline, but no difference when compared to the control. Citicoline has the potential to improve patient mobility in supratentorial intracerebral hemorrhage stroke, but in terms of improvement in functional status and neurological impairment requires further research.